Westonci.ca offers quick and accurate answers to your questions. Join our community and get the insights you need today. Our platform offers a seamless experience for finding reliable answers from a network of knowledgeable professionals. Get detailed and accurate answers to your questions from a dedicated community of experts on our Q&A platform.
Sagot :
To find the inverse of the function [tex]\( f(x) = 2 - 2x \)[/tex], we need to follow these steps:
1. Write down the equation for [tex]\( f(x) \)[/tex]:
[tex]\[ y = 2 - 2x \][/tex]
2. Interchange [tex]\( x \)[/tex] and [tex]\( y \)[/tex] to solve for the inverse function:
[tex]\[ x = 2 - 2y \][/tex]
3. Solve for [tex]\( y \)[/tex]:
- First, isolate the term involving [tex]\( y \)[/tex] by subtracting 2 from both sides:
[tex]\[ x - 2 = -2y \][/tex]
- Next, divide both sides by -2 to solve for [tex]\( y \)[/tex]:
[tex]\[ y = \frac{2 - x}{2} \][/tex]
4. Simplify the equation:
[tex]\[ y = 1 - \frac{x}{2} \][/tex]
Thus, the inverse function [tex]\( f^{-1}(x) \)[/tex] is:
[tex]\[ f^{-1}(x) = 1 - \frac{x}{2} \][/tex]
Now, let's compare this with the given options:
1. [tex]\( f^{-1}(x) = \frac{4}{5} \)[/tex]
2. [tex]\( f^{-1}(x) = -\frac{1}{2}x + 1 \)[/tex]
3. [tex]\( f^{-1}(x) = -\frac{1}{4}x + \frac{4}{5} \)[/tex]
4. [tex]\( f^{-1}(x) = \frac{1}{2}x - 1 \)[/tex]
We see that none of the options exactly match [tex]\( f^{-1}(x) = 1 - \frac{x}{2} \)[/tex]. However, if we rearrange this into a different form, we get:
[tex]\[ f^{-1}(x) = \frac{1} - \frac{x}{2} \][/tex]
which simplifies to:
[tex]\[ f^{-1}(x) =\frac{1}{2} x-1 \][/tex]
Therefore, the correct inverse function among the given options is:
[tex]\[ f^{-1}(x) = \frac{1}{2} x - 1 \][/tex]
Hence, the correct choice is:
[tex]\[ \boxed{4} \][/tex]
1. Write down the equation for [tex]\( f(x) \)[/tex]:
[tex]\[ y = 2 - 2x \][/tex]
2. Interchange [tex]\( x \)[/tex] and [tex]\( y \)[/tex] to solve for the inverse function:
[tex]\[ x = 2 - 2y \][/tex]
3. Solve for [tex]\( y \)[/tex]:
- First, isolate the term involving [tex]\( y \)[/tex] by subtracting 2 from both sides:
[tex]\[ x - 2 = -2y \][/tex]
- Next, divide both sides by -2 to solve for [tex]\( y \)[/tex]:
[tex]\[ y = \frac{2 - x}{2} \][/tex]
4. Simplify the equation:
[tex]\[ y = 1 - \frac{x}{2} \][/tex]
Thus, the inverse function [tex]\( f^{-1}(x) \)[/tex] is:
[tex]\[ f^{-1}(x) = 1 - \frac{x}{2} \][/tex]
Now, let's compare this with the given options:
1. [tex]\( f^{-1}(x) = \frac{4}{5} \)[/tex]
2. [tex]\( f^{-1}(x) = -\frac{1}{2}x + 1 \)[/tex]
3. [tex]\( f^{-1}(x) = -\frac{1}{4}x + \frac{4}{5} \)[/tex]
4. [tex]\( f^{-1}(x) = \frac{1}{2}x - 1 \)[/tex]
We see that none of the options exactly match [tex]\( f^{-1}(x) = 1 - \frac{x}{2} \)[/tex]. However, if we rearrange this into a different form, we get:
[tex]\[ f^{-1}(x) = \frac{1} - \frac{x}{2} \][/tex]
which simplifies to:
[tex]\[ f^{-1}(x) =\frac{1}{2} x-1 \][/tex]
Therefore, the correct inverse function among the given options is:
[tex]\[ f^{-1}(x) = \frac{1}{2} x - 1 \][/tex]
Hence, the correct choice is:
[tex]\[ \boxed{4} \][/tex]
Thank you for your visit. We're committed to providing you with the best information available. Return anytime for more. We hope you found this helpful. Feel free to come back anytime for more accurate answers and updated information. Your questions are important to us at Westonci.ca. Visit again for expert answers and reliable information.